Effect of PVA-co-MMA copolymer on the physical, mechanical, and thermal properties of tropical wood materials - Islam, Md. Saiful; Hamdan, Sinin; Ahmad @ Ayob, Mansor; Hasan, Mahbub; Hassan, Azman; Mohamad Kassim, Mohamad Haafiz; Jawaid, Mohammad (Hindawi Publishing Corporation, 2014)
The present study demonstrates the effect of copolymer on the physical, mechanical, and thermal properties of tropical wood and wood polymer composites (WPCs). Mixed monomers of methyl methacrylate (MMA) and polyvinyl alcohol (PVA) were effectively impregnated into the cellular structure of several types of tropical wood, which then underwent a catalyst-thermal process to polymerize and form WPC. The manufacturing of WPC was confirmed through Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopic (SEM) analysis. The SEM observation showed that polymer converted from monomers filled up wood cell cavities and tightly interacted with wood matrix. The X-ray diffraction results reveal that the degree of crystallinity was significantly improved upon impregnation with PVA-co-MMA copolymer. The modulus of elasticity (MOE) and compressive modulus were found to be significantly higher after treatment with MMA/PVA indicating improvement of mechanical properties of the wood samples. In addition, the modified WPC had lower water absorption compared to their corresponding raw samples. It is interesting to note that thermogravimetric (TGA) analysis shows an extensive improvement in thermal properties of WPC.